(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2026)
The surface of mobile phones and internet technologies has visibly magnified way in to information and transformed both the social and business landscapes. On this ground, Mobile commerce has become the present-day inclination to perform business. E-commerce business models and procedures conducted on mobile terminal are referred to as M-commerce. The development of mobile devices and its significant growth and penetration rate have created new opportunities for mobile technology, which is leading to the rapid growth of M-commerce. However, its adoption followed by degree of utilization is low in Nepal as compared to other developed nations. The study has made an effort to recognize some determinants that leverage M-commerce adoption in the midst of Nepalese customers based on traditional technology acceptance models. By adopting a quantitative approach and conducting a survey among three hundred ninety (N = 390) Nepalese customers, the study revealed that perceived usefulness, perceived ease of use, perceived trust, perceived cost and perceived privacy are statistically significant and could leverage M-commerce adoption in Nepal. As recommended by the findings, effective promotional activities among final customers to habituate with M-commerce would generate more strike on its adoption. This study adds to the current M-commerce literature by presenting an overview based on perceptions from Nepal.